2015
DOI: 10.1049/iet-map.2014.0559
|View full text |Cite
|
Sign up to set email alerts
|

Patch size reduction of rectangular microstrip antennas by means of a cuboid ridge

Abstract: An effective approach to reduce the patch size in rectangular patch microstrip antennas is presented. The proposed approach is based on inductively loading the patch using a cuboid ridge. A theoretical background of the approach using the transmission line model has been provided. A prototype of the proposed antenna is fabricated and measured. The results, advantages and limitations of the proposed approach are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…It is also observed that the arc projection is more effective in reducing the resonant frequency for the thinner substrates. In other words, similar to the phenomenon that occurs for the cuboid ridge in a rectangular patch microstrip antenna [11], it is the ratio of the projection height to the substrate thickness (h r /h) that determines how effective the projection is.…”
Section: Parametric Study Of the Arc Projectionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is also observed that the arc projection is more effective in reducing the resonant frequency for the thinner substrates. In other words, similar to the phenomenon that occurs for the cuboid ridge in a rectangular patch microstrip antenna [11], it is the ratio of the projection height to the substrate thickness (h r /h) that determines how effective the projection is.…”
Section: Parametric Study Of the Arc Projectionmentioning
confidence: 95%
“…As mentioned in Section I, the idea of arc projection inspired from the impressive effect of a cuboid ridge on the miniaturization of the rectangular patch antenna with its theoretical explanation has been explained in [11] in detail. The role of cuboid ridge is basically like a short stub in transmission line model of the antenna that loads the antenna inductively and reduces the resonance frequency.…”
Section: Configuration Of the Antennamentioning
confidence: 99%
See 2 more Smart Citations
“…8 and 9, the simulated directivity [13] values include 0.38 dB at 6.07 GHz, 0.91 dB at 9.25 GHz, 2.9 dB at 15.79 GHz, and 3.72 dB at 23.41 GHz. 8 and 9, the simulated directivity [13] values include 0.38 dB at 6.07 GHz, 0.91 dB at 9.25 GHz, 2.9 dB at 15.79 GHz, and 3.72 dB at 23.41 GHz.…”
Section: Directivitymentioning
confidence: 99%